Colonization of Snow by Microorganisms as Revealed Using Miniature Raman Spectrometers-Possibilities for Detecting Carotenoids of Psychrophiles on Mars? - Jehlička, Jan; Culka, Adam; Nedbalová, Linda (Astrobiology, 2016)
We tested the potential of a miniaturized Raman spectrometer for use in field detection of snow algae pigments. A miniature Raman spectrometer, equipped with an excitation laser at 532 nm, allowed for the detection of carotenoids in cells of Chloromonas nivalis and Chlamydomonas nivalis at different stages of their life cycle. Astaxanthin, the major photoprotective pigment, was detected in algal blooms originating in snows at two alpine European sites that differed in altitude (Krkonoše Mts., Czech Republic, 1502 m a.s.l., and Ötztal Alps, Austria, 2790 m a.s.l.). Comparison is made with a common microalga exclusively producing astaxanthin (Haematococcus pluvialis). The handheld Raman spectrometer is a useful tool for fast and direct field estimations of the presence of carotenoids (mainly astaxanthin) within blooms of snow algae. Application of miniature Raman instruments as well as flight prototypes in areas where microbes are surviving under extreme conditions is an important stage in preparation for successful deployment of this kind of instrumentation in the framework of forthcoming astrobiological missions to Mars. Key Words: Snow algae-Chloromonas nivalis-Chlamydomonas nivalis-On-site field detection-Raman spectroscopy-Astaxanthin. Astrobiology 16, 913-924.
Keywords: Chlamydomonas; sníh; Snow; Ice Cover; Spectrum Analysis, Raman; Miniaturization; ledový příkrov; Carotenoids; Chlorophyta; Czech Republic; Ramanova spektroskopie; miniaturizace; karotenoidy; Česká republika